Restorative Strategies Following Vital Pulp Therapy: Does the Coronal Restoration Determine Success? A Scoping Review - Esma Nur Güney (Journal of Endodontics and Restorative Dentistry, 2026)
Background: Vital pulp therapy (VPT) aims to preserve pulp vitality, but long-term success may also depend on the definitive coronal restoration. The influence of restorative strategy on VPT outcomes remains unclear. This scoping review aimed to map randomized controlled clinical evidence on coronal restorative strategies used with VPT, focusing on restoration performance and its relationship with VPT success. Methods: The final searches of PubMed/MEDLINE, Scopus, and the Web of Science Core Collection were completed on 1 August 2026. Randomized controlled clinical trials involving primary or permanent teeth treated with VPT and reporting at least one coronal restoration-related clinical outcome were included. The review was reported in accordance with the PRISMA Extension for Scoping Reviews (PRISMA-ScR); study selection and data extraction were performed by a single reviewer, and findings were synthesized descriptively. Results: Thirteen randomized clinical studies met the eligibility criteria. Restorative approaches included stainless steel crowns (SSCs), glass-ionomer-based restorations, composite resin, Cention-N, amalgam, modified open-sandwich restorations, 3D-printed resin crowns, zirconia crowns, and lithium-disilicate endocrowns. SSCs showed favorable restorative performance in several primary molar studies, and some trials reported higher treatment survival or pulpotomy success compared with glass ionomer or amalgam. However, other studies found no significant differences in VPT success between restorative strategies. In several trials, restoration deterioration did not correspond with biological VPT failure, or the relationship was not directly analyzed. Conclusion: Coronal restoration is an important component of VPT, but restorative performance and biological VPT success are distinct outcomes. Current evidence does not support a universally superior restorative strategy after VPT. Future trials should evaluate both outcomes separately using standardized criteria and longer follow-up.